NMDA receptor GluN2A/GluN2B subunit ratio as synaptic trait of levodopa-induced dyskinesias: from experimental models to patients - Mellone, Manuela; Stanic, Jennifer; Hernandez, Ledia F.; Iglesias, Elena; Zianni, Elisa; Longhi, Annalisa; Prigent, Annick; Picconi, Barbara; Calabresi, Paolo; Hirsch, Etienne C.; Obeso, Jose A.; Di Luca, Monica; et al. (Frontiers in Cellular Neuroscience, 2015)
Levodopa-induced dyskinesias (LIDs) are major complications in the pharmacological management of Parkinson’s disease (PD). Abnormal glutamatergic transmission in the striatum is considered a key factor in the development of LIDs. This work aims at i. characterizing NMDA receptor GluN2A/GluN2B subunit ratio as a common synaptic trait in rat and primate models of LIDs and in dyskinetic PD patients, and ii. validating the potential therapeutic effect of a cell-permeable peptide interfering with GluN2A synaptic localization on the dyskinetic behavior of these experimental models of LIDs. Here we demonstrate an altered ratio of synaptic GluN2A/GluN2B-containing NMDA receptors in the striatum of levodopa-treated dyskinetic rats and monkeys as well as in post-mortem tissue from dyskinetic PD patients. The modulation of synaptic NMDA receptor composition by a cell-permeable peptide interfering with GluN2A subunit interaction with the scaffolding protein PSD-95 leads to a reduction in the dyskinetic motor behavior in the two animal models of LIDs. Our results indicate that targeting synaptic NMDA receptor subunit composition may represent an intriguing therapeutic approach aimed at ameliorating levodopa motor side effects.